Are signs and symptoms in cardiovascular rehabilitation correlated with heart rate variability? An observational longitudinal study - Takahashi, Carolina [UNESP]; Ribeiro, Felipe [UNESP]; Vanzella, Laís Manata [UNESP]; Lima, Isabelle Maina [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Christofaro, Diego Giulliano Destro [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Wiley, 2020)
Aim: To analyze the correlation between the appearance of signs/symptoms during a cardiovascular rehabilitation program and linear indexes of the heart rate variability (HRV) at rest. Methods: To carry out the present observational longitudinal study, 48 patients were analyzed. The protocol was divided into two stages. First, the patients had their personal details collected, and the autonomic modulation at rest was evaluated by HRV. Second, they underwent 36 sessions of the cardiovascular rehabilitation program to evaluate signs/symptoms. Then, just for analysis of the data, they were divided into two groups: the group without signs/symptoms (n = 26; 65.15 ± 9.7 years); and the group with signs/symptoms (n = 22; 66.77 ± 14.4 years). The HRV indexes were compared by ancova. The effect size was measured through the partial eta-squared. Pearson's and Spearman's correlations (P < 0.05) were used to analyze the data, and linear regression was applied. Results: A total of 103 signs/symptoms occurred. The group with signs/symptoms presented lower values of HRV indexes when compared with the group without signs/symptoms, especially for the parasympathetic indexes with a large effect size. The root mean square of successive differences (rMSSD), percentage of adjacent RR intervals with a difference of duration >50 ms (pNN50), high-frequency spectral component (HF) varying from 0.15 to 0.4 Hz (expressed as ms2), dispersion of the points perpendicular to the line of identity and represents the instantaneous record of the beat-to-beat variability (SD1) and SD1/scatter of points along the identity line and represents the HRV in long-term records (SD2) index presented a negative correlation with the appearance of signs/symptoms. When the linear regression was applied, the rMSSD, SD1 and SD1/SD2 showed negative values of β (P < 0.05). Conclusions: Patients with lower HRV are more likely to have signs/symptoms. The rMSSD, pNN50, HF (expressed as ms2), SD1 and SD1/SD2 index presented a negative correlation with the appearance of signs/symptoms. For rMSSD, SD1 and SD1/SD2, the lower the values of these HRV indexes, the greater the risk of appearance of signs/symptoms. Geriatr Gerontol Int 2020; ••: ••–••.
Keywords: autonomic nervous system; rehabilitation services; signs and symptoms